A community‐based, mixed‐methods study of the attitudes and behaviors of men regarding modern family planning in Nigeria. Issue 1 (October 2016) - Akaba, Godwin; Ketare, Nathaniel; Tile, Wilfred
Abstract: Objectives: To investigate the knowledge, attitudes, and extent of involvement of men in family planning in Nigeria, and to evaluate spousal communication regarding family planning. Methods: A community‐based, mixed‐methods study enrolled participants in Gwagwalada, Abuja, Nigeria between January 11 and June 30, 2012. Quantitative surveys including semi‐structured interviews were used to collect information from married men regarding their knowledge and attitudes to modern family planning. The qualitative components constituted focus group discussion sessions and in‐depth interviews that included married men, married women, religious leaders, community leaders, and family‐planning providers. Results: Quantitative surveys were completed by 152 men; 99 (65.1%) reported that they would accompany their wives to family‐planning clinics in the future, 116 (76.3%) reported approving of the use of modern contraception by their wives, and 132 (86.8%) reported wanting to know more about family planning. Both quantitative and qualitative aspects of the study indicated that husbands were the major decision makers regarding family size, choice of contraceptive, and pregnancy timing. Conclusion: In terms of fertility goals and family planning, men were the primary decision makers; consequently, obtaining their support and commitment to family planning is of crucial importance in Nigeria.